Fruit and vegetable consumption and health outcomes: an umbrella review of observational studies. (18th August 2019) - Angelino, Donato; Godos, Justyna; Ghelfi, Francesca; Tieri, Maria; Titta, Lucilla; Lafranconi, Alessandra; Marventano, Stefano; Alonzo, Elena; Gambera, Angelo; Sciacca, Salvatore; Buscemi, Silvio; Ray, Sumantra; et al.
Abstract: The aim of this study was to provide a comprehensive evaluation of current evidence on fruit and vegetable consumption and health outcomes. A systematic search for quantitative syntheses was performed. Several criteria, including study design, dose–response relationship, heterogeneity and agreement of results over time, and identification of potential confounding factors, were used to assess the level of evidence. The strongest (probable) evidence was found for cardiovascular disease protection; possible evidence for decreased risk of colon cancer, depression and pancreatic diseases was found for fruit intake; and colon and rectal cancer, hip fracture, stroke, depression and pancreatic diseases was found for vegetable intake. Suggestive and rather limited associations with other outcomes have been found. Evidence of potential confounding by sex and geographical localisation has been reported. Despite findings are consistent enough for hypothesising causation (at least for cardiovascular-related outcomes), further studies are needed to clarify the role of potential confounding factors.